2017
DOI: 10.4103/0970-2113.217567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of efflux pump inhibitors on the susceptibility of Mycobacterium tuberculosis to isoniazid

Abstract: Background:Mycobacterium can develop drug resistance (DR) by mutation of its existing gene. However, the existence of DR without mutation shows the need to look for an alternative mechanism such as the role of efflux pumps. In this study, we examined the effect of efflux pump inhibitors on isoniazid (INH) susceptibility in clinical isolates of Mycobacterium tuberculosis (Mtb).Materials and Methods:Resazurin microtiter assay was used to examine the effect of efflux pump inhibitors on minimum inhibitory concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…In this study, CPZ combinations with CIP or LEV have markedly reduced the MIC of resistance isolates. Our result agreed with studies previously carried out against Mycobacterium spp [78,79]. It has been found that CPZ had a significant bactericidal effect [6,75] in addition to the efflux pump inhibitor action when tested for their effect on antibiotic resistance [79,80].…”
Section: Plos Onesupporting
confidence: 92%
“…In this study, CPZ combinations with CIP or LEV have markedly reduced the MIC of resistance isolates. Our result agreed with studies previously carried out against Mycobacterium spp [78,79]. It has been found that CPZ had a significant bactericidal effect [6,75] in addition to the efflux pump inhibitor action when tested for their effect on antibiotic resistance [79,80].…”
Section: Plos Onesupporting
confidence: 92%
“…Antibiotic adjuvants or potentiators are compounds that enhance antibiotic activity by inactivating resistance mechanism (Wright, 2016). As a proof of concept, it was shown that the MIC of isoniazid decreased in the presence of various categories of efflux pump inhibitors in clinical isolates of M. tuberculosis (Jaiswal et al, 2017). Efflux pump inhibitors should thus be considered to improve current TB therapy (Pule et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the utility of potentiating combinations, anchored by SPT, to circumvent drug resistance and potentially restore (partial) susceptibility where genetically drug-resistant mutants preexist for one of the partner compounds. We applied combination screens utilizing (i) chlorpromazine (CPZ), a phenothiazine whose complex and unresolved mechanism of action involving disruption of the mycobacterial electron transport chain ( 23 ) has been implicated in efflux pump inhibition ( 24 ), and (ii) fusidic acid (FA), a translational inhibitor with demonstrated (albeit moderate) activity in vitro ( 25 , 26 ). FA was selected owing to its potential for repositioning as anti-TB agent and because it possesses a unique mechanism of action, specifically, inhibition of bacterial protein synthesis by binding to elongation factor G (EF-G) ( 27 ).…”
Section: Introductionmentioning
confidence: 99%